π-Extended diphosphonium-bridged ladder stilbenes: water-soluble fluorophores with up to eight annulated rings - Senn, Sebastian; Mörsdorf, Jean-Marc; Bertrams, Maria-Sophie; Kerzig, Christoph; Ballmann, Joachim (Chemical science, 2025)
Diphosphapentalene-derived P-heterocyclic materials with two directly fused phospholes are fairly scarce, at least in comparison to their simpler congeners containing only one phosphole entity. To fill that void, π-conjugated naphtho-fused phospholo[3,2-b]phosphole dications were prepared via in situ oxidation of the corresponding diphosphines. In the case of one specific naphtho-annulation pattern, a hitherto unprecedented bis-(Δ2-phosphetene) dication was formed selectively and isolated as a colorless powder. DFT modelling studies revealed that this bis-(Δ2-phosphetenium) salt is produced via single electron transfer steps, while all the phospholo[3,2-b]phosphole salts may either be generated via their P-diylidic counterparts or via similar radical mechanisms. Exploiting this knowledge, the dicationic phospholo[3,2-b]phosphole isomer of the bis-(Δ2-phosphetenium) salt was isolated as well. In view of the high fluorescence quantum yields of these naphtho-fused phospholo[3,2-b]phosphole salts in aqueous solution, linearly π-extended anthraceno-fused derivatives were developed in order to bathochromically shift their emissions into the biological window. While detailed optoelectronic studies confirmed our expectations, the utmost remarkable observation is that even the anthraceno-fused materials were found to be sufficiently soluble in water, despite the fact that these fluorophores comprise up to eight fused rings.
Gesehen am 22.01.2026